2022
DOI: 10.1093/mnras/stac1998
|View full text |Cite
|
Sign up to set email alerts
|

Tracing a decade of activity towards a yellow hypergiant. The spectral and spatial morphology of IRC+10420 at au scales

Abstract: The fate of a massive star during the latest stages of its evolution is highly dependent on its mass-loss history and geometry, with the yellow hypergiants being key objects. We present near-IR interferometric observations of the famous yellow hypergiant IRC +10420 and blue spectra taken between 1994-2019. Our 2.2 μm GRAVITY/VLTI observations attain a spatial resolution of ∼5 stellar radii and spatially resolve the hot emission in the K-band tracing the gas via Na i doublet emission and the Brγ emission. Our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
0
3
1
Order By: Relevance
“…The equivalent widths of the intense Na I lines from the YHG IRC +10420 [6] are about three times higher than for HD 179821, for which we measured values of −1.0670 ± 0.015 Å and −0.9231 ± 0.018 Å. Recent spatially resolved observations revealed that the Na I emission in IRC +10420 and Hen 3-1379 is confined within a compact spherical envelope around the star [50,123]. The emission lines in our spectrum are symmetric, and their wavelengths coincide with the systemic velocity of the star.…”
Section: Hd 179821 (=Rafgl 2343 Iras 19114+0002 V1427 Aql)contrasting
confidence: 48%
See 1 more Smart Citation
“…The equivalent widths of the intense Na I lines from the YHG IRC +10420 [6] are about three times higher than for HD 179821, for which we measured values of −1.0670 ± 0.015 Å and −0.9231 ± 0.018 Å. Recent spatially resolved observations revealed that the Na I emission in IRC +10420 and Hen 3-1379 is confined within a compact spherical envelope around the star [50,123]. The emission lines in our spectrum are symmetric, and their wavelengths coincide with the systemic velocity of the star.…”
Section: Hd 179821 (=Rafgl 2343 Iras 19114+0002 V1427 Aql)contrasting
confidence: 48%
“…Na I emission is a clear indicator for circumstellar material. It has been reported from the NIR spectra of numerous evolved massive stars: (i) the YHGs ρ Cas, V509 Cas, Hen 3-1379 (the Fried Egg Nebula), IRC +10420 [70,123], and the IRC +10420 analog IRAS 18357-0604 [124], (ii) most of the B[e]SGs [21,29,125], and (iii) also many luminous blue variables [21,53]. The equivalent widths of the intense Na I lines from the YHG IRC +10420 [6] are about three times higher than for HD 179821, for which we measured values of −1.0670 ± 0.015 Å and −0.9231 ± 0.018 Å.…”
Section: Hd 179821 (=Rafgl 2343 Iras 19114+0002 V1427 Aql)mentioning
confidence: 99%
“…The atomic sodium doublet emission (Na at 2.20 𝜇m) has been previously detected in various astrophysical environments (e.g., evolved massive stars; Hanson et al 1996;Koumpia et al 2022) including MYSOs (Porter et al 1998;Pomohaci et al 2017). Due to its low ionization potential (5.1 eV) and its co-existence in energetic environments with the hydrogen recombination line (Br𝛾), the physical process responsible for this emission has been under debate.…”
Section: Na and He : Two New Tracers Of The Star/disc Interfacementioning
confidence: 99%
“…Emission from magnetically aligned grains is the most likely origin of the observed continuum polarisation, which suggests a strong role of surface activity of a convective nature and magnetic fields in the star's recent mass-loss history. At milliarcsecond spatial resolution, the outflow produced by IRC +10420 has the shape of an hourglass nebula, possibly induced by high rotation and latitude dependent mass-loss (Koumpia et al 2022).…”
Section: The Warm Hypergiantsmentioning
confidence: 99%